Inclusion of cybercrimes within the subject-matter jurisdiction of the International Criminal Court: Limits of possibility - Aissa, Samsar (The International tax journal, 2025)
Cybercrime is one of the most dangerous emerging crimes threatening the international community. Its ability to evolve and spread rapidly, infiltrating various aspects of life, heightens its danger. However, the means available to combat these crimes are insufficient to address the issue effectively. This necessitates including cybercrimes within the International Criminal Court's subject-matter jurisdiction. However, there are several obstacles that limit the feasibility of this inclusion. This study will elaborate on the most significant of these obstacles.